2015
DOI: 10.12738/estp.2015.6.2829
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Secondary School Students’ Perceptions of Mathematics Education Quality on Mathematics Anxiety and Achievement

Abstract: The two aims of this study are as follows: (i) to compare the differences in mathematics anxiety and achievement in secondary school students according to their perceptions of the quality of their mathematics education via a cluster analysis and (ii) to test the effects of the perception of mathematics education quality on anxiety and achievement via structural equation modeling. The research was designed using a causal design; the mathematics education quality comprised the independent variable, whereas mathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
1
3
0
1
Order By: Relevance
“…This implies that most of them are demotivated during math classes and, hence, new alternatives to the traditional methodology (teaching the theory included in a math textbook and solving the exercises of such a book) are needed; this conclusion is consistent with the literature [3]. As previously commented in the literature section, demotivation and even anxiety are frequently present in Mathematics learning [5][6][7][8][9][10], so innovative methodological approaches such as the one presented herein are usually positively valued by the student body. In keeping with this, it was observed that, in general terms, the proposed methodology in this paper enhances students' motivation to learn (as reflected by the more active participation of students in the classroom).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This implies that most of them are demotivated during math classes and, hence, new alternatives to the traditional methodology (teaching the theory included in a math textbook and solving the exercises of such a book) are needed; this conclusion is consistent with the literature [3]. As previously commented in the literature section, demotivation and even anxiety are frequently present in Mathematics learning [5][6][7][8][9][10], so innovative methodological approaches such as the one presented herein are usually positively valued by the student body. In keeping with this, it was observed that, in general terms, the proposed methodology in this paper enhances students' motivation to learn (as reflected by the more active participation of students in the classroom).…”
Section: Discussionsupporting
confidence: 70%
“…One of the subjects that, in general terms, is often associated with lower interest levels and higher difficulties in students is mathematics [5][6][7][8]. Furthermore, in many cases mathematics can provoke anxiety in students [9,10]. In fact, mathematics is one of the most requested subjects in private tuition, since the knowledge that students assimilate in their high school classes is often insufficient in many cases.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A recent study on students' perceptions of teaching approaches found that the degree to which students considered their class to be teacher-centred had a detrimental effect on their disposition toward maths (Pampaka & Williams, 2016). Ciftci (2015) found that student perceptions of the quality of their mathematics education had an effect on their performance and anxiety. Though research on perceptions of IBME has been conducted, it remains underrepresented in the literature relative to studies about the efficacy of such approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been conducted in Turkey to examine student achievement on TIMSS, PISA, or PIRLS data (Akyüz, 2014;Anıl, 2009;Atar, 2014;Özberk et al, 2017;Özdemir, 2016;). However, a few studies conducted in Turkey to examine student academic achievement on national large scale assessment such as Placement Test Results (SBS), Student Achievement Determination Exam (ÖBBS), Transition from Primary to Secondary education (TEOG) or on students' GPA in schools (Börkan & Bakış, 2016;Çiftçi, 2015;Engin-Demir, 2009;Gelbal, 2008;.…”
Section: Introductionmentioning
confidence: 99%